St. Stephan's Dom Kirche, Vienna - Tombleson, William, b. ca. 1795 (engraver):::Creator::::::::::::; Batty, Robert, 1789-1848 (artist):::Contributor:::::::::::: (United Kingdom; Rodwell & Martin; London)
Engraving with a view of St. Stephans church in Vienna and people walking in the plaza